Analisis Pengaruh Penanaman Modal Dalam Negeri (PMDN) dan Penanaman Modal Asing (PMA) terhadap Pertumbuhan Ekonomi di Provinsi Daerah Istimewa Yogyakarta - Armenita, Elysabeth Sintya; Wuri, Josephine; Hardanti, Yuliana Rini; Harnoto, Laurentius Bambang (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2024)
Economic growth is an indicator that reflects a region's progress and its people's welfare. This study aims to analyze the effect of Domestic Investment (PMDN) and Foreign Investment (PMA) on Economic Growth. The research method used is a panel data regression analysis method of the variables of Domestic Investment (PMDN), Foreign Investment (PMA) and Economic Growth in DIY Province during the period 2016-2022. Partially, Domestic Investment (PMDN) influences Economic Growth in Yogyakarta Special Region Province. Foreign Investment (PMA) does not influence Economic Growth in the Special Region of Yogyakarta Province. Simultaneously, domestic and foreign investments influence economic growth in the Special Province of Yogyakarta. Based on the analysis results, policy measures are needed to strengthen the influence of PMDN on economic growth in the Special Province of Yogyakarta.